Processing of Green Composites - Rakesh, Pawan Kumar; Singh, Inderdeep; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book is a collection of chapters focusing on green composite materials. The selection of natural fibers and polymer matrix materials, and the bonding between them forms an essential aspect of this book. The book discusses the chemical treatment of natural fibers and their compatibility with different matrix materials. The growing applications of composites in every day life ranging from automobiles to aerospace are also discussed. The book highlights the importance of processing of natural fiber reinforced composite materials to enhance their mechanical strength and performance. The contents of this book will be beneficial for students, researchers and industry professionals working on composite materials. .
Preface -- Introduction -- Introduction to Green Composites -- Mechanical behavior of natural fiber reinforced green composite -- Feasibility study of fly ash as filler in banana fiber reinforced hybrid composite -- Mechanical properties of biodegradable composites subjected to hydro-thermal environment -- Effects of chemical treatment on the natural fiber reinforced composites -- Physico-mechanical properties of Himalayan nettle fabric reinforced polyester composite -- Role of Silk Fiber Reinforced Composites in Engineering and Medical Applications -- Machining on natural fiber reinforced PLA composite -- Index -- Bibliography.
Keywords: Ceramic materials; Green chemistry; Mechanics, Applied; Solids; Biomaterials; Ceramics; Green Chemistry; Solid Mechanics; Biomaterials